NILAI PENDIDIKAN AGAMA HINDU DALAM GEGURITAN KALA TATTWA - I Wayan Janur Divayana (JAPAM (Jurnal Pendidikan Agama), 2024)
ABSTRACT Geguritan is a Balinese Hindu culture that contains many meanings, noble values ​​and uniqueness in it. The uniqueness contained in geguritan kala tattwa as a literary work includes aspects of tattwa, ethics and leadership. However, many people think that geguritan is only a literary work that is only sung or developed. The problems discussed include the structure of geguritan when tattwa and the value of education in geguritan kala tattwa. This type of research is qualitative research. In this study the sampling technique used was purposive sampling. The methods used in this research are literature and interview methods. After collected, it will be analyzed with analysis techniques. The analysis techniques used in this research are steps to reduce, present, and draw conclusions or verify. The results obtained based on research include, (1) The structure of the tattwa geguritan includes themes, characters, settings and messages. The theme of the geguritan is the philosophy of the metatah ceremony, the figures of the geguritan include Lord Shiva, Dewi Uma, Bhatara Indra, Bhatara Wisnu, Bhatara Brahma and Detya. The setting of this geguritan is samurdra and heaven. While the mandate contained in this geguritan is love and morality. (2) The values ​​contained in geguritan kala tattwa include tattwa values, ethical values ​​and literary values.